2020
DOI: 10.1371/journal.pone.0238921
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and lipid profile of mare colostrum and milk of the quarter horse breed

Abstract: The objective of this study was to characterize the chemical composition and lipid profile of colostrum and milk of purebred Quarter Horse mares. Thirty-four (34) purebred mares were selected, which were then separated into groups according to age, birth order and lactation stage. Colostrum samples were collected in the first six hours after delivery and milk samples from the 7 th postpartum day, with intervals of 14 days until the end of lactation. The samples were refrigerated and sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 22 publications
20
25
0
1
Order By: Relevance
“…TA B L E 1 Descriptive statistics of the concentration of fatty acids in milk of grazing Pega donkeys ratio lower than 1 (Table 2). Barreto et al (2020) have reported similar values of 18:0 (1.6%) and SFA/UFA ratio (0.95%) in mare milk. The fatty acid profile is similar between horses and donkeys, with high PUFA content for donkey milk (Salimei & Fantuz, 2002).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…TA B L E 1 Descriptive statistics of the concentration of fatty acids in milk of grazing Pega donkeys ratio lower than 1 (Table 2). Barreto et al (2020) have reported similar values of 18:0 (1.6%) and SFA/UFA ratio (0.95%) in mare milk. The fatty acid profile is similar between horses and donkeys, with high PUFA content for donkey milk (Salimei & Fantuz, 2002).…”
Section: Discussionsupporting
confidence: 54%
“…was related to the concentration of 16:0, which is the major SFA in donkey milk (Table 1). The concentration of 16:0 in mare milk is similar to donkey milk, and it has been reported to increase until 120 DIM (Barreto et al 2020). Previous studies have demonstrated a reduction in milk 16:0 as a function of lactation stage (Gastaldi et al, 2010;Martemucci & D'Alessandro, 2012;Valle et al, 2018).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Кобылье молоко является ценным пищевым продуктом, т. к. химические вещества, входящие в его состав, близки к женскому молоку [1][2][3][4][5][6][7]. Отличительной особенностью кобыльего молока является его высокая биологическая ценность и усвояемость [8,9].…”
Section: Introductionunclassified